TAC3 and TACR3 mutations in familial hypogonadotropic hypogonadism reveal a key role for Neurokinin B in the central control of reproduction - (:unkn) unknown (NATURE PUBLISHING GROUP, 2009)
The timely secretion of gonadal sex steroids is essential for the initiation of puberty, the postpubertal maintenance of secondary sexual characteristics and the normal perinatal development of male external genitalia. Normal gonadal steroid production requires the actions of the pituitary-derived gonadotropins, luteinizing hormone and follicle-stimulating hormone. We report four human pedigrees with severe congenital gonadotropin deficiency and pubertal failure in which all affected individuals are homozygous for loss-of-function mutations in TAC3 (encoding Neurokinin B) or its receptor TACR3 (encoding NK3R). Neurokinin B, a member of the substance P-related tachykinin family, is known to be highly expressed in hypothalamic neurons that also express kisspeptin(1), a recently identified regulator of gonadotropin-releasing hormone secretion(2). These findings implicate Neurokinin B as a critical central regulator of human gonadal function and suggest new approaches to the pharmacological control of human reproduction and sex hormone-related diseases.
Keywords: ARCUATE NUCLEUS; TACHYKININ RECEPTORS; MORPHOLOGIC EVIDENCE; RAT HYPOTHALAMUS; HORMONE NEURONS; EXPRESSION; DYNORPHIN; MICE; KISSPEPTIN; DEFICIENCY